An Attempt to Measure the Trends in Shadow Employment in Poland : The Transition Probabilities out and into Shadow Employment Using the LFS Data Augmented by the Results of a Dedicated Survey Performed by CASE in 2007 - Walewski, Mateusz (2012)
This paper presents the results of an attempt to use the combined results of the dedicated survey performed by CASE in 2007 and Polish LFS data in order to: (a) analyze the development of the shadow employment in Poland in years 2003-2008 and, (b) analyze the transition probabilities in and out of shadow employment. The estimated share of shadow workers in total employment in Poland in years 2003-2008 was increasing until 2006 and then started to decrease in the years 2007 and 2008. Other results are in line with one of the main conclusions of the CASE study from 2007 suggesting that shadow employment is more a way of coping with lack of other employment opportunities than an equivalent or even superior alternative to any legal employment contracts. On the other hand those who enter shadow employment are more active part of the group having problems with finding full time/open term employment. They are much more inclined to cope with their situation by entering some form of self-employment than to stay passive and depend on social assistance.